Different ZnII cation coordination geometries in di‐μ‐acetato‐bis2‐chloro‐6‐[(pyridine‐2‐ylmethylimino)methyl]phenoldizinc(II) chloroform monosolvate. (11th October 2013) - Kim, Young‐Inn; Lee, Jin Young; Song, Young‐Kwang; Kang, Sung Kwon
Abstract : In the title compound, di‐μ‐acetato‐κ 2 O : O ;κ 2 O : O ′‐bis[(6‐chloro‐2‐( E )‐[(pyridin‐2‐yl)methylimino]methylphenolato‐κ 3 N, N ′, O )zinc(II)], [Zn2 (C13 H10 ClN2 O)2 (C2 H3 O2 )2 ]·CHCl3, the Zn II cation adopts a five‐coordinate geometry and is coordinated by two N atoms and one O atom of a tridentate 6‐chloro‐2‐( E )‐[(pyridin‐2‐yl)methylimino]methylphenolate ligand and two O atoms of two bridging acetate groups, but their coordination geometries differ. One Zn II cation adopts a distorted trigonal bipyramidal geometry and the other a square‐pyramidal geometry. The two acetate ligands bridge two Zn II cations with mono‐ and bidentate coordination modes. The title compound exhibits a strong emission at 460 nm upon excitation at 325 nm with a quantum yield of 23.1%.